ANALISIS KOMPARATIF MODEL DESAIN INSTRUKSIONAL ADDIE, DICK & CAREY, DAN ASSURE DALAM MENINGKATKAN KUALITAS PEMBELAJARAN FISIKA SERTA KEMAMPUAN LITERASI DAN NUMERASI SISWA: SEBUAH SYSTEMATIC LITERATURE REVIEW - Parihin Parihin; Joko Suseno; Velya Pramesthi Putri Ragil; Dirgantara Wicaksono (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT Physics learning in the 21st century requires not only mastery of scientific concepts but also well-developed scientific literacy and numeracy skills as fundamental competencies for evidence-based decision-making. However, the effectiveness of instructional design models in fostering these competencies remains varied, highlighting the need for a comprehensive comparative investigation. This study aimed to analyze the characteristics, effectiveness, and educational implications of three major instructional design models: ADDIE (Analysis, Design, Development, Implementation, Evaluation), Dick and Carey (Systems Approach Model), and ASSURE (Analyze Learners, State Objectives, Select Strategies, Utilize Technology, Media and Materials, Require Learner Participation, Evaluate and Revise) within the context of physics education. The study employed a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines through the stages of identification, screening, eligibility assessment, and inclusion of studies published between 2021 and 2026. A total of 42 eligible journal articles were synthesized. The findings indicate that the ADDIE model is more adaptable for instructional material development, the Dick and Carey model provides a highly systematic framework for strengthening students' numeracy skills, whereas the ASSURE model is more effective in integrating instructional media and promoting active learner engagement to enhance scientific literacy. These findings suggest that the effectiveness of instructional design is context-dependent and should be aligned with the characteristics of physics content, instructional objectives, and targeted competencies, while also providing a conceptual foundation for developing more adaptive instructional models in future research. ABSTRAK Pembelajaran fisika pada abad ke-21 menuntut penguasaan konsep ilmiah yang diimbangi dengan kemampuan literasi sains dan numerasi sebagai fondasi pengambilan keputusan berbasis bukti. Namun, implementasi desain instruksional yang tepat untuk mendukung kedua kompetensi tersebut masih menunjukkan variasi efektivitas sehingga diperlukan kajian komparatif yang komprehensif. Penelitian ini bertujuan menganalisis karakteristik, efektivitas, serta implikasi penerapan model ADDIE (Analysis, Design, Development, Implementation, Evaluation), Dick & Carey (Systems Approach Model), dan ASSURE (Analyze Learners, State Objectives, Select Strategies, Utilize Technology, Media and Materials, Require Learner Participation, Evaluate and Revise) dalam pembelajaran fisika. Penelitian menggunakan metode Systematic Literature Review (SLR) dengan mengacu pada pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) melalui tahapan identifikasi, penyaringan, penilaian kelayakan, dan inklusi terhadap artikel yang diterbitkan pada periode 2021–2026. Sebanyak 42 artikel memenuhi kriteria untuk disintesis. Hasil kajian menunjukkan bahwa model ADDIE lebih adaptif untuk pengembangan perangkat pembelajaran, Dick & Carey memberikan struktur sistematis yang mendukung penguatan numerasi, sedangkan ASSURE lebih efektif dalam mengoptimalkan pemanfaatan media pembelajaran dan partisipasi aktif peserta didik guna meningkatkan literasi sains. Temuan ini menegaskan bahwa efektivitas desain instruksional bersifat kontekstual sehingga pemilihannya perlu disesuaikan dengan karakteristik materi fisika, tujuan pembelajaran, dan kompetensi yang ingin dikembangkan, sekaligus menjadi dasar pengembangan model pembelajaran yang lebih adaptif pada penelitian berikutnya.